Factors that Influence Doctors' Preference for Working in the Village with Government Policy - Almira Nur Amalia (HM Publisher, 2021)
One of the problems faced by the Indonesian people is the unequal distribution of doctors, especially in villages and other disadvantaged areas. One of the causes is the low interest of medical students and doctors to work in the area. The government as the highest authority holder should have made efforts to solve a state problem as outlined in the form of government policy. Recent research conducted by Kharinnisa et al in 2016 identified several factors that influenced the interest of medical students to work in rural areas. This study was conducted to determine the relationship of these factors with government policy. This study is a descriptive qualitative study in the form of a literature study. Of the eight factors, only half are supported by government regulations, namely having visited rural areas, career opportunities, income potential, facilities in rural areas and factors not yet supported by government regulations include university location, family economic status, closeness to family and spouse. Therefore it is necessary to study the formation of government policies that can support all these factors along with the proper implementation of these policies.